Scholars, Science, Education (Damyanov, 2015) [In Bulgarian] - B.V. Toshev (University of Sofia, 2016)
Дамянов, Д. (2015). Будители, наука, образование: статии и интервюта (1990-2014). София: изд. Захарий Стоянов, 615 с. ISBN 978954-09-0924-0